A numerical study of ionospheric profiles for mid-latitudes - S.-R. Zhang; X.-Y. Huang (Annales Geophysicae)
This paper presents a numerical model and results for the mid-latitude ionospheric profile below the peak of the F2-layer. The basis of the model is the solving of equations for four ionic species O+, NO+, O+2 and N+2, as well as the meta-stable O+(2D) and O+(2P). Diffusion and wind-induced drifts and 21 photo-chemical reactions are also taken into account. Neutral atmospheric density and temperature are derived from the MSIS86 model and solar extreme ultraviolate irradiance from the EUV91 model. In an effort to obtain a more realistic ionospheric profile, the key point at foF2 and hmF2 is fitted from the simulation to observations. The model also utilizes the vertical drifts derived from ionosonde data with the help of the Servo model. It is shown that the ionospheric height of peak can be reproduced more accurately under the derived vertical drifts from the Servo theory than with the HWM90 model. Results from the simulation are given for Wuchang (30.5°N, 114.4°E) and Wakkanai (45.6°N, 141.7°E), showing the profile changes with season and solar activity, and the E-F valley structure (the depth and the width). This simulation also reveals the importance of meta-stable ions and dynamical transport processes on the formation of the F1-ledge and F1-F2 valley.